(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The landscape, bearing certain pressure from the society, simultaneously has an aesthetic potential and actively affects the emotional and psychological comfort of a person. Among the many factors affecting the aesthetic qualities of the landscape (relief, vegetation, water, etc.), colour is also separated. The color diversity of the landscapes is impossible to appreciate with only using eyes. The article presents a unique methodology for separating colour shades, which are one of the important aesthetic factors of the landscape. For the first time, an attempt was made to distinguish the color tones that have a great influence on the aesthetic qualities of landscapes and to group them by analyzing the spectral curves of satellite images․ In contrast to the traditional field method, satellite images allow us to assess color tones over a short period of time and over a large area. Red, green and blue are considered the main physiological colours, and almost all true colours can be obtained by the combination of these three radiations. An attempt was made to separate the colors in the landscapes by analyzing spectral curves in green (543–578 nm), red (650–680 nm), blue (458–523 nm) spectral ranges of the Sentinel-2A, Sentinel 2B TCI (true color image) space images taken in the summer with a resolution of 10 m. In a professional software environment, 50 classes were obtained using "unsupervised" classification method, and for each class, the curves with the average values of spectral reflection of three visible colour ranges were obtained. By grouping the classes, a map of five colour groups (blue-green, green, red, gray and yellow, white) of the landscapes of Syunik Region was created for the summer season. Since the most important factor of colour harmony is the balance of colour shades, an attempt was made to determine the colour diversity of landscapes. Based on the obtained colour groups, in the summer season the colour diversity of the landscapes of Syunik Region was asssessed and mapped using Shannon’s coefficient of heterogeneity. As a result, it was found that 52% of the landscapes of Syunik Region have green colouring in summer. The latter is considered a positive feature of the aesthetic appeal of landscapes and has a calming effect on a person. White colour has the smallest percentage share. 36% of the territory of the region has a high and very high diversity indicator, and 17.6% has a very low degree of diversity. In summer, the North-Eastern part of the region, the areas adjacent to the lower and middle streams of the Vorotan River, the Voghji and Meghri River basins are distinguished by colour diversity. However, from the point of view of aesthetic perception, the average degree of diversity is highly assessed, which is 27.2% in Syunik Region. The Southern part of Syunik has an average degree of diversity, especially the valley areas of the Araks River, the area of the Spandaryan reservoir.